2023
DOI: 10.1002/jcu.23461
|View full text |Cite
|
Sign up to set email alerts
|

The use of radiomics and machine learning for the differentiation of chondrosarcoma from enchondroma

Abstract: Purpose To construct and compare machine learning models for differentiating chondrosarcoma from enchondroma using radiomic features from T1 and fat suppressed Proton density (PD) magnetic resonance imaging (MRI). Methods Eighty‐eight patients (57 with enchondroma, 31 with chondrosarcoma) were retrospectively included. Histogram matching and N4ITK MRI bias correction filters were applied. An experienced musculoskeletal radiologist and a senior resident in radiology performed manual segmentation. Voxel sizes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…It is imperative to ascertain these to fully evaluate the model's real-world utility. Further DL model development plans from radiographs could be the differential diagnosis of enchondroma and chondrosarcoma from plain radiographs, as previously performed from MRI and CT with ML, texture analysis, and radiomics [17][18][19]. Due to the challenges and constraints associated with the histological diagnosis of peripheral chondrosarcoma and enchondroma, the DL model could offer an additional valuable assessment to assist in determining the most suitable treatment for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to ascertain these to fully evaluate the model's real-world utility. Further DL model development plans from radiographs could be the differential diagnosis of enchondroma and chondrosarcoma from plain radiographs, as previously performed from MRI and CT with ML, texture analysis, and radiomics [17][18][19]. Due to the challenges and constraints associated with the histological diagnosis of peripheral chondrosarcoma and enchondroma, the DL model could offer an additional valuable assessment to assist in determining the most suitable treatment for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study focused on utilizing MRI radiomics for distinguishing chondrosarcoma from enchondroma. In this research, pathology served as the gold standard for comparison, and different models were evaluated, all of which demonstrated strong performance in this diagnostic task [19]. These imaging modalities are usually used for treatment planning after suspicion has been raised with a traditional radiograph and is thus not available for diagnostic aid.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have investigated the value of MR image-based radiomics in chondroid tumors [9,10,21]. These studies have shown promising results in the discrimination of enchondroma and chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that certain texture parameters that reflect intratumoral heterogeneity can serve as valuable prognostic markers [8]. Texture analysis with MR images have shown the potential for differentiating chondrosarcoma and enchondromas [9,10]. While there have been several attempts to use radiomics from anatomic imaging, the value of SPECT/CT radiomics have not yet been evaluated in bone tumors.…”
Section: Introductionmentioning
confidence: 99%